Numerical and experimental analysis of the mechanical properties of hardox steel - Keleş, Mehmet (My University, 2002)
Main purpose of the thesis is examine mechanical properties of the HARDOX steel by experimental methods. The tension test which is done during the thesis is not limited HARDOX in addition to that two more steels WELDOX and St52 are used Generally HARDOX is an abrasion resistant plate and WELDOX is an extra high strength structural plate. During the thesis in addition to tensile test, bending, hardness and micro structure tests were done with HARDOX steel. Furthermore for HARDOX steel to see the affect of experiment speed to mechanical properties of specimen tensile tests were repeated under different strain rates. This thesis consists of five chapters. First chapter is a general introduction about the thesis. Second chapter contains different properties and usage conditions of HARDOX and WELDOX steels. In this chapter mechanical properties, their cutting bending and shearing conditions of these steels, and their development process are given. Third chapter is a materials and methods section. In this section performed experiments, their specimen dimensions, experiment conditions and experiment tools are introduced. In fourth the last chapter all experiment results ( microstructure photographs, experiment graphics and data etc.) obtained in the thesis are given. In this section all experiment results represented and discussed. Fifth chapter contains a numerical model which is used to make tensile test in computer. Last chapter is a result section and an evaluation about the thesis. November 2002 Mehmet Keleş Bu tezdeki esas amaç HARDOX çeliğinin mekaniksel özelliklerini deneysel olarak incelemektir. Bu incelemeyi yaparken yapılan çekme deneylerinde HARDOX çeliğinin yanı sıra WELDOX ve St52 çelikleri içinde yapılmıştır. Genel anlamda HARDOX bir aşınma sacı, WELDOX ise ekstra mukavemetli bir yapı çeliğidir. Bu tezde HARDOX çeliği için çekme, eğme, basma ve mikro yapı incelesi deneyleri yapılmıştır. Ayrıca HARDOX çeliği için çekme hızının deneysel etkisini görmek için çekme deneyi değişik çekme hızlarıyla tekrarlanmıştır. Tez dört kısımdan oluşmaktadır. İlk kısım tezle alakalı eren bir giriş bölümüdür. İkinci kısım HARDOX ve WELDOX çeliklerinin değişik özelliklerinin ve kullanım bilgileri içeren bir bölümdür. Bu kısımda HARDOX ve WELDOX çeliklerinin mekanik özellikleri, kesme ( Alevle ), bükme ve kesme ( Makasla ) şartlarını ve bu çeliklerin geliştirilme sürecinden bahsetmektedir. Üçüncü kısım malzeme ve tezde takip edilen yolla ilgili bir kısımdır. Bu bölümde yapılan deneyler ve bunların hangi standartlara göre yapıldıkları, numune boyutları, deney şartları, deney cihazları ve özelliklerinin anlatıldığı bir kısımdır. Dördüncü bölüm tezde elde edilen tüm deney bilgilerinin ( Mikro yapı resimleri, deney grafik ve sonuçları vb. ) verildiği kısımdır. Bu kısımda laboratuar koşullarında elde edilen verileri sunulup tartışılmıştır. Beşinci bölüm bilgisayarda çekme testi analizi yapan bir sonlu elemanlar modeli içerir. Son bölümde ise tezin genel bir değerlendirilmesi yapılmıştır. Kasım 2002
Keywords: Makina Mühendisliği; Mühendislik; Mühendislik mekaniği